Genetic mapping of quantitative trait locus for the leaf morphological traits in a recombinant inbred line population by ultra‐high–density maps across multi‐environments of maize (Zea mays). (11th September 2019) - Zhang, Kuangye; Lv, Xiangling; Li, Fenghai; Wang, Jia; Yu, Hongwei; Li, Jianbo; Du, Wanli; Diao, Yulin; Wang, Jiaxu; Weng, Jianfeng
Abstract: Leaf is the main organ of photosynthetic reaction of plants. Studying the genetic mechanism that affects the leaf shape is very important for the improvement of maize production. In this study, a RIL population, derived from a cross between Ye478 and Qi319, was planted in four different environments, and six leaf morphological traits were measured, including the leaf angle of first leaf above ear, the leaf angle of first leaf below ear, leaf orientation value, leaf area of first leaf above ear, leaf area of ear and leaf area of first leaf below ear. By combining with a genetic map containing 4, 602 bin markers, 39 QTLs associated with leaf morphological traits were identified. Among them, four QTLs explained more than 10% of the phenotypic variance, and the QTL qLOV8‐2 which controlled LOV not only had a phenotypic contribution rate of 13.86% but also was detected in four environments, which could be considered as a stable major QTL. These results provide useful information for understanding the molecular mechanisms controlling maize leaf morphological traits.